The role of blink reflex R1 latency as an electrophysiological marker in diabetic distal symmetrical polyneuropathy. Issue 1 (January 2020) - Lai, Yun-Ru; Huang, Chih-Cheng; Chiu, Wen-Chan; Liu, Rue-Tsuan; Tsai, Nai-Wen; Wang, Hung-Chen; Lin, Wei-Che; Cheng, Ben-Chung; Su, Yu-Jih; Su, Chih-Min; Hsiao, Sheng-Yuan; Wang, Pei-Wen; et al.
Highlights: Patients with DSPN had longer blink R1, R2, and contralateral R2 latencies. Blink R1 latency is valuable in auxiliary diagnosis in DSPN. Blink R1 latency was independently associated with CAS. Abstract: Objective: Studies showed a relatively prolonged blink R1 latency in patients with diabetic distal symmetrical polyneuropathy (DSPN) compared to that without DSPN. We tested the hypothesis that blink R1 latency would provide a diagnostic alternative to nerve conduction studies (NCS) in DSPN and act as a marker of the severity of NCS abnormalities in DSPN. Method: A total of 109 patients with type 2 diabetes underwent blink reflex studies and NCS. We used the composite amplitude scores of nerve conductions (CAS), which consisted of motor (tibial, peroneal and ulnar) and sensory (sural and ulnar) amplitudes for estimating the severity of NCS. Results: Patients with DSPN had longer blink R1, R2, and contralateral R2 latencies ( P  < 0.0001, P  = 0.001, and P  = 0.031, respectively) and higher CAS ( P  < 0.0001). Area under curve on receiver operating characteristic curve analysis in diagnosing occurrence of DSPN in blink R1 latency was 0.772 ( P  < 0.0001). Multiple linear regression analysis showed that blink R1 latency was independently associated with CAS. Conclusion: Blink R1 latency may be valuable in auxiliary diagnosis and in determining the severity of NCS abnormalities in DSPN. Significance: Blink R1 latency can be added as a supplemental marker of severity of NCS in DSPN, especially if the patient's sural amplitudes has a floor effect.